"Bee-Bot only speaks Irish." A sociocultural investigation of the use of programmable floor robots for second language learning and developing computational thinking skills in the early years of primary school. - Nic Réamoinn, Susan (Trinity College Dublin. School of Education. Discipline of Education, 2024)
This thesis presents a sociocultural theory (SCT) investigation of the use of robotics for second language learning (SLL) and computational thinking (CT) skills development in the early years of primary school. The research intervention combines a playful storytelling robotics-based activity with the Irish language within a play session. Jeanette Wing, revived the area of CT in (2006, p. 44) noting that CT should be added "to every child's analytical thinking." Current research indicates that technological tools have a positive impact on the development of CT skills when integrated with other curricular areas in primary school (Alimisis & Moro, 2016; Angeli & Valanides, 2020; Angeli et al., 2016; Bers, 2020; Bers et al., 2012; Hassenfeld & Bers, 2020). This research intervention contributes to the field of CT skills development as well as second language learning in the early years of primary school, through the integration of robotics and Irish, in an English medium classroom. The researcher deemed design-based research (DBR) as the most appropriate methodology to answer the research questions while using both qualitative and quantitative data collection methods. The research intervention was developed through an iterative design cycle of two one pilot cycles and a third pilot cycle over six weeks. The final iteration, cycle four, comprised of a six-week intervention using Bee-Bot (programmable floor robot) as part of a playful activity to promote second language learning with 22 children in a junior infant class (aged 5-6 years). The children worked in small groups to programme Bee-Bot to support their storytelling through Irish. The results of this research activity were positive with feedback from the children and the teacher of increased interest and use of the Irish language, observed language gains; identification and development of CT skills; and positive meaningful engagement through Irish amongst the children. The findings provide an insight into the opportunities that a technological tool provides during a playful activity with this young age group as well as outlining the potential parallels between the language learning process and CT skills development. As the Irish curriculum moves towards a more integrated model (NCCA, 2023) the analysis of the children's experiences during this research activity along with their language and CT skill development offers an interesting insight for early year's language educators and curriculum developers in Ireland.
APPROVED
Keywords: Primary School; Robotics; Floor-programmable robotics; Bee-Bot; Second lanaguage learning; Computational thinking; Irish; Gaeilge; Early years